2021
DOI: 10.1039/d1re00073j
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modelling of Pt/γ-Al2O3–Cl catalysts formulation changes in n-heptane reforming

Abstract: Bridging the gap between kinetic model conception and catalyst design is targeted in catalytic naphtha reforming process development. New catalysts are continuously optimised in order to achieve higher selectivity in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This may explain why recently reported experimental results showed that the impact of morphology is less predominant than chlorine contents on reforming catalytic activities and selectivities. 26…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain why recently reported experimental results showed that the impact of morphology is less predominant than chlorine contents on reforming catalytic activities and selectivities. 26…”
Section: Resultsmentioning
confidence: 99%
“…For n -heptane reforming, model reaction for naphtha reforming, Said-Aizpuru et al showed that the hydroisomerization selectivity follows a non-monotonous trend as a function of chlorine content and that the isomerization selectivity may also depend on the nature of alumina support. 25,26 This observation clearly calls for the need of establishing refined atomic scale descriptors of the catalyst's bifunctionality and to quantify more precisely the intimacy criterion. 27 Even if the intimacy criterion for mass transport is respected and there is adequate conversion it does not guarantee perfect selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…8 A number of literatures have reported that some parameters affected the catalytic performance of the naphtha reforming. 1,5,[9][10][11] However, the combined impact of the various variables with each other has not been reported. Investigating the reaction of catalytic naphtha reforming is very difficult owing to the many reactions borne out by the hundreds of hydrocarbons that are found in it.…”
Section: Introductionmentioning
confidence: 99%
“…Their results show that the nature of the catalytic limiting steps for different reaction pathways and the physicochemical properties of the catalyst influence the reaction selectivity. 9 Although the results of the above-mentioned articles can prove the importance of modeling in a complex reaction as catalytic reforming, there is still a need to investigate this reaction with other effective parameters. Statistical assessment accomplished by Parsafard et al presented that catalyst molar ratio, temperature and time on stream are influential factors that enable us to effectively estimate isomerization reaction with RSM on the mesoporous active samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation